An Analysis of Reinforcement Implemented by English Teachers at MAN Kota Pariaman - Jayanti, Ade Dwi (LPPM Politeknik Raflesia, 2023)
There are 2 types of reinforcement strategies such as: reward dan punishment. Based on the problems found at the beginning of the research, the purpose of this research was to find out the type, frequency, time, and reasons for reward and punishment used by English teachers as a strategy in classroom management. This type of research was descriptive research. The sample in this research was all English teachers. Data obtained through observation, interviews, and questionnaires. The research findings show that English teachers only use intrinsic reward and positive punishment types. The frequency of using rewards is 128 times, while the frequency of using punishments is 29 times. The teachers uses reward and punishment at the beginning, core and end of learning activities. Furthermore, teachers have several reasons for using rewards including: 1) fulfill students’ academic achievement, 2) succeed in achieving learning goals, 3) help students to improve behavior, 4) create an orderly class, 5) improve student concentration on assignment, 6) create peacefull interactions between teachers and students, 7) monitor student behavior. Besides that, teachers also have several reasons for using punishment, including; 1) ensuring students’ interest in learning, 2) warning students to behave appropriately, 3) creating a calm classroom atmosphere, 4) creating discipline in class, 5) preventing negative behavior, 6) obeying school rules.